Attentional Effort of Beginning Mindfulness Training Is Offset With Practice Directed Toward Images of Natural Scenery. (June 2017) - Lymeus, Freddie; Lundgren, Tobias; Hartig, Terry
Mindfulness involves curious and detached attention to present experience. Long-term mindfulness practice can improve attentional control capabilities, but practice sessions may initially deplete attentional resources as beginners struggle to learn skills and manage distractions. Without using skills or effort, people can have mindful experiences in pleasant natural environments; natural scenery may therefore facilitate mindfulness practice. Twenty-seven participants completed an 8-week mindfulness course; 14 served as waiting-list controls. We tested participants' attention every other week before and after 15-min sessions of conventional mindfulness practice, mindfulness practice with nature images, or rest with nature images (controls). Mindfulness practice incurred attentional effort; it hampered performance gains seen in controls during practice/rest sessions, and attentionally weak participants completed fewer course exercises. Viewing nature images during practice increasingly offset the effort of mindfulness practice across the 8 weeks. Bringing skill-based and nature-based approaches together offers additional possibilities for understanding and facilitating mindfulness and restorative states.